Synthesis, Structural Analysis and Thermal Behavior of New 1,2,4-Triazole Derivative and Its Transition Metal Complexes - Ali Taleb Bader; Nada Ahmed Rasheed Al-qasii; Ahmed Hassen Shntaif; Maryam El Marouani; Mohammed Idaan Hassan AL Majidi; László Trif; Mohammed Boulhaoua (Universitas Gadjah Mada, 2022)
Cobalt(II), nickel(II), and copper(II) complexes containing bidentate ligands )5-(4-nitrophenyl)-4-((4-phenoxybenzylidene)amino)-4H-1,2,4-triazole-3-thiol) could be synthesized by the condensation reaction between 1,2,4-triazole derivative and p-phenoxy benzaldehyde. The ligand and its complexes were characterized by various spectroscopic techniques such as FTIR, UV-visible, 1H and 13C-NMR, element analysis, molar conductance, and magnetic susceptibility test. The new ligand was exploited as a ligand to coordinate with Co(II), Ni(II), and Cu(II) by a molar ratio of 1:2 (metal:ligand). The prepared complexes (C1, C2, and C3) were exposed to thermo-gravimetric analysis (TGA/DTG) under an inert atmosphere to investigate their thermal stability. The ligand (L) degradation was also investigated as a reference. The results indicated that the complexes proposed structures had an octahedral geometry.